Dispatches: A Town Called Kozarac
A detailed account of the killing, beating, rape and expulsion inflicted on the Muslims in Kozarac, northern Bosnia, by the Serbian authorities. The film features detailed accounts from eyewitnesses of the manner and effects of 'ethnic cleansing' and denials of the ‘ethnic cleansing’ by Serbian forces, as well as interviews with Bosnians living in Watford (England), Bosnian refugees, and the Serbian mayor of Prijedor.